Multiple recursive division explanations for image classification problems - Gorokhovatskyi, Oleksii; Peredrii, Olena; Teslenko, Oleh (Національний технічний університет "Харківський політехнічний інститут", 2025)
In this paper, the approach to search for multiple explanations of the CNN image classification case is proposed. Research results. The core of the method is recursive division (RD), that performs the perturbation of the input image with hiding different rectangular parts. The explanation is represented as a complementary images pair (CIP): two images that allow us to visualize the parts of the image which are important enough to change the class of the input image when hidden and at the same time are important enough to preserve the initial classification result when visible. The parameters of RD method are discussed to choose the criteria to stop the processing when few explanations are found or the further processing requires too much time and/or memory resources. Two approaches to merge multiple CIP back to single explanation using SLIC segmentation were proposed. They allowed us to reduce the useful image explanation area and sometimes find more visually attractive CIP compared to previous RD implementations. Such merging is not strictly required just multiple CIP explanations are good enough for analysis of the CNN.

У цій статті пропонується підхід до пошуку множинних пояснень випадку класифікації зображень CNN. Результати дослідження. Основою методу є рекурсивний поділ (RD), який виконує збурення вхідного зображення з приховуванням різних прямокутних частин. Пояснення представлено у вигляді пари зображень, які доповнюють один одного (CIP): така пара зображень дозволяє нам візуалізувати частини зображення, які є достатньо важливими, щоб змінити клас вхідного зображення, коли вони приховані, і водночас є достатньо важливими, щоб зберегти початковий результат класифікації, коли вони видимі. Обговорюються параметри методу RD для вибору критеріїв зупинки обробки, коли знайдено декілька пояснень або подальша обробка вимагає забагато часу та/або ресурсів пам'яті. Було запропоновано два підходи до об'єднання кількох CIP назад в одне пояснення за допомогою сегментації SLIC. Вони дозволили нам зменшити корисну область пояснення зображення та іноді знайти візуально привабливіші CIP порівняно з попередніми реалізаціями RD. Таке об'єднання не є суворо обов'язковим, якщо достатньо лише кількох пояснень CIP для аналізу CNN.
Множинні пояснення рекурсивним поділом для проблем класифікації зображень
Keywords: image classification; black-box; explainability; image perturbation; hiding parts; recursive division; complementary image pair; класифікація зображення; чорна скриня; пояснювальність; збурення зображення; приховування частин; рекурсивний поділ; пара доповнюючих зображень